CONCEPTUAL ORIGINS OF LEGAL LINGUISTICS - GALDIA, Marcus (Comparative Legilinguistics, 2021)
This essay is a survey of methods applied and topics scrutinized in legal-linguistic studies. It starts with the elucidation of the epistemic interest that led to the emergence and to the subsequent expansion of the mainstream legal-linguistic knowledge that we dispose of today. Thus, the essay focuses upon the development of problem awareness in the emerging legal-linguistic studies as well as upon the results of research that might be perceived as the state of the art in the mainstream legal linguistics. Meanwhile, some methodologically innovative tilts and twists that enrich and inspire contemporary legal linguistics are considered as well. Essentially, this essay traces the conceptual landscape in which the paradigms of legal-linguistic studies came about. This conceptual landscape extends from the research into the isolated words of law and the style used by jurists to the scrutiny of legal texts and legal discourses in all their socio-linguistic complexity. Within this broad frame of reference, many achievements in legal-linguistic studies are mentioned in order to sketch the consequences of processes in which legal-linguistic paradigms take shape. The author concludes upon a vision of legal linguistics called pragmatic legal linguistics as the newest stage in the intellectual enterprise that aims to pierce the language of the law and by so doing to understand law better.